Design, synthesis and characterization of fatty acid esters in food flavours and nutritional supplements - Li, Cheng (2014)
Flavor esters are the most important and versatile components of ﬂavoring compounds and fragrances. These esters have been widely used in the food, beverage, fine cosmetic, non-cosmetic and pharmaceutical industries. Methionol is an alcohol with low odour threshold ranging from about 1 to 3 ppm and imparts powerful sensory notes described as meaty, boiled potato-like, vegetable-like, savory or toasted cheese-like. 2-Phenethyl alcohol is a colorless liquid with a pleasant floral odour with a mild, warm and rose-honey-like note of moderate to poor tenacity. It has been wildly found in a variety of essential oils such as rose, hyacinth, aleppo pine, orangeblossom, ylangylang, allium, anise, carnation, geranium, neroli and champaca. This material is therefore used as a fragrance ingredient in many compounds, particularly when rose odour is desired. Novel methionol derived fatty acid esters of up to 14 carbon fatty acid and 2-phenethyl alcohol derived fatty acid esters of up to 18 carbon fatty acid were synthesized by both chemical and lipase catalysed esterification between fatty acids and methionol or 2-phenethyl alcohol, respectively. The high acid- and heat-stability of methionyl esters and 2-phenethyl esters meet the requirement of food matrix. Most importantly, the sensory test showed that fatty acid carbon chain length had important effects on the flavour attributes of methionyl esters and 2-phenethyl esters.